KAJIAN POLA PERGERAKAN DI PROPINSI LAMPUNG - Rahayu Sulistyorini; Dwi Heriyanto (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2010)
Highway in Lampung is the main transportation mode to support internal transportation system. Especially to develop regional transportation in Trans Sumatera and people interaction between Java and Sumatra islands. This paper try to analys travel pattern in Lampung as base information which useful to transportation planning in this province.The result of analys show that travel pattern in Lampung is dominated by through traffic from other area like Java to other province in Sumatera (Bengkulu and South Sumatera). The most heavy loading in road network is in Sumatera East Coast Highway wich linking between South Sumatera, Mesuji, Menggala, Seputih Banyak, Sukadana, Labuhan Maringgai and Bakauheni. The other heavy load is in road which linking Bengkulu, Kasui, Blambangan Umpu, Bandar Lampung, tegineneng, Bandar Jaya Labuhan Maringgai and Panjang. Within a few years in a future, it’s important to developing other alternative beside road network like railway network and mass transportation.